ANALISIS BREAK EVEN POINT SEBAGAI DASAR PENGAMBILAN KEPUTUSAN PENETAPAN HARGA JUAL PADA USAHA KECIL DAN MENENGAH (UKM) DI KOTA BANDA ACEH - Nuzuliani Abdullah; Fazli Syam BZ (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this research is to analyse the break even point on selling price determination, to know the difference of selling price between the one which is stated by SMEs in trading sector in Banda Aceh and the one which is the result of break even point analysis, and also to know the correlation between the break even point and selling price. Type of this research is statistical descriptive analysis. Population in this research are SMEs listed in Dinas Perindustrian, Perdagangan, Koperasi, dan UKM in Banda Aceh. Based on certain criterias, there are 30 SMEs as the samples of the research. This research shows that there is a difference betweet the rate of selling price determined by the SMEs and break even point analysis result. Based on correlation test, there is positive significant correlation between selling price and break even point.